Reconstruction of Maqasid Syariah Value’s in the Islamic Political Culture - Khumaini, Fahmi (http://jagadalimussirry.com/, 2019)
Islam is a complete view of life, that is the integral of religion with politics, law and community. The reform of society requires referring to Islam that is a reform of religion-politic taking inspiration from the Quran and Sunnah. In this current situation, the unfinished problem is the practice of corruption that takes personal or group advantage. It happens because of the disappearance of values of aqida and the way of thinking which contain s Islamic purposes, tillit destruct s the moral system of society and economic gap. The improvement of Culture and political purpose fundamentally are needed both philosophically and practical. The term politic means care (ri'ayah), reform (ishlah), establish (taqwim), guidance (irsyad) and educate, Thus there is a common with the meaning of maqasid Syaria fundamentally, that emphasize s the improvement continuously in the system or role related to the personal culture or in society, and as an instrument of social design that produce an individual and society in increasing the quality of education, morals and aqida in.